KEBIJAKAN HUKUM PIDANA TERHADAP PERSEKUSI DALAM PERSPEKTIF KEADILAN RESTORATIF DAN HAM DI INDONESIA - Satrio Muniarto; Sri Iin Hartini; Baharudin Saleh Ingratubun (Collegium Studiosum Journal, 2026)
The purpose of this research is to analyze the Criminal Law Policy Against Persecution from a Restorative Justice and Human Rights Perspective in Indonesia and to identify the obstacles encountered in its implementation in Indonesia. The method used in this research is normative juridical research, namely examining laws and regulations, legal norms, and legal theory, and carefully observing how these laws are implemented and their impact on society. Furthermore, at the beginning of the research, the author conducted an inventory of positive law, which is a fundamental preliminary activity for conducting legal research. The research results show that the crime of persecution has not been regulated as a stand-alone offense in Law Number 1 of 2023 concerning the Criminal Code, so law enforcement still uses existing criminal provisions in accordance with the elements of the act. Furthermore, resolving the crime of persecution through a restorative justice approach is more effective in achieving case resolution through an admission of guilt by the perpetrator, an apology, restitution of the victim's losses, and reconciliation between the parties, thus providing justice, legal certainty, and benefits, without neglecting the protection of human rights.